Acompañamiento de los padres de familia en el proceso educativo de los estudiantes de primero de bachillerato – de la Unidad Educativa San Juan del periodo lectivo 2015-2016 - Guerrero Sánchez, Ingrid Mariela (2016)
The present investigation work is of psychological character, which had the purpose of determining the importance of parents or representatives’ contribution during the educational process of the students. The main modality of investigation is addressed toward to a documental investigation in which scientific books were used to the elaboration of the theoretical mark, theoretical posture and the field investigation since the researcher was immersed in the Educational Community, who was in contact with the students and in constant dialogue with the Campus’ authorities, and mainly with the psychologist of the DECE, in what concerning information was obtained to sustain the topic of this work. The investigation’s methodology was applied with an exploratory, a descriptive and an explanatory focus; due to the investigation was based on the human community, so it was necessary the data tabulation with the objective of making the corresponding statistical process. The obtaining data were applied to surveys, based on a questionnaire strategically developed and in relation to the identified indicators in the process of operationalization of variables. The work evidenced as a result a high index of dissatisfaction on the participation of parents or representatives, for what the necessity of the elaboration of an accompaniment plan was identified, which has to be worked in sessions with the parents or representatives, to promote the team work and to clarify the roles of the participants inside the education.